Metabolic alteration of Catharanthus roseus cell suspension cultures overexpressing geraniol synthase in the plastids or cytosol - Saiman, Mohd Zuwairi; Miettinen, Karel; Mustafa, Natali Rianika; Choi, Young Hae; Verpoorte, Robert; Schulte, Anna Elisabeth (Springer, 2018)
Previous studies showed that geraniol could be an upstream limiting factor in the monoterpenoid pathway towards the production of terpenoid indole alkaloid (TIA) in Catharanthus roseus cells and hairy root cultures. This shortage in precursor availability could be due to (1) limited expression of the plastidial geraniol synthase resulted in a low activity of the enzyme to catalyze the conversion of geranyl diphosphate to geraniol; or (2) the limitation of geraniol transport from plastids to cytosol. Therefore, in this study, C. roseus’s geraniol synthase (CrGES) gene was overexpressed in either plastids or cytosol of a non-TIA producing C. roseus cell line. The expression of CrGES in the plastids or cytosol was confirmed and the constitutive transformation lines were successfully established. A targeted metabolite analysis using HPLC shows that the transformed cell lines did not produce TIA or iridoid precursors unless elicited with jasmonic acid, as their parent cell line. This indicates a requirement for expression of additional, inducible pathway genes to reach production of TIA in this cell line. Interestingly, further analysis using NMR-based metabolomics reveals that the overexpression of CrGES impacts primary metabolism differently if expressed in the plastids or cytosol. The levels of valine, leucine, and some metabolites derived from the shikimate pathway, i.e. phenylalanine and tyrosine were significantly higher in the plastidial- but lower in the cytosolic-CrGES overexpressing cell lines. This result shows that overexpression of CrGES in the plastids or cytosol caused alteration of primary metabolism that associated to the plant cell growth and development. A comprehensive omics analysis is necessary to reveal the full effect of metabolic engineering.